Digital Synergy and Strategic Vision: Unlocking Sustainability-Oriented Innovation in Saudi SMEs - Karam Zaki; Abrar Alhomaid; Ashraf Ghareb; Hany Shared; Alaa Raslan; Gamal S. A. Khalifa; Ahmed K. Elnagar (Administrative Sciences)
This research examines the proposition that enhancing sustainable innovation can be particularly effective when the focus is on strategy, machine learning, and digitalization. The study specifically targets the complex interactions among strategic alignment (SA), sustainability-oriented innovation (SOI), and digital transformation (DT) within small and medium-sized enterprises (SMEs) in Saudi Arabia, particularly within the service sector. A moderated mediation framework was constructed to analyze the influence of SA on SOI, the mediating role of DT, and the moderating effect of strategic orientation (SO). Data were collected through structured surveys from 339 SMEs using a quantitative research design and a cross-sectional methodology. The partial least squares structural equation modeling (PLS-SEM) technique was employed to validate the proposed framework and hypotheses. The results indicate that SA significantly boosts SOI, with DT acting as a strong mediator in this connection. Furthermore, SO moderates the relationships between SA and SOI, SA and DT, and DT and SOI, highlighting its essential role in shaping the dynamics of sustainable innovation. These findings emphasize the necessity of aligning strategic initiatives with digital advancements to foster innovation that achieves a balance among economic, social, and environmental objectives. This study contributes to existing literature by filling the research gap regarding SOI and DT in Saudi SMEs and offers practical insights for SMEs facing sustainability challenges. Future research should delve deeper into digital technology configurations, industry-specific contexts, and cross-national applications to improve the applicability of these findings.